2015
DOI: 10.1021/acs.molpharmaceut.5b00007
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Delivery with Cell Surface Binding and Cell Penetrating Peptide Amphiphile Nanospheres

Abstract: A drug delivery system designed specifically for oligonucleotide therapeutics can ameliorate the problems associated with the in vivo delivery of these molecules. The internalization of free oligonucleotides is challenging, and cytotoxicity is the main obstacle for current transfection vehicles. To develop nontoxic delivery vehicles for efficient transfection of oligonucleotides, we designed a self-assembling peptide amphiphile (PA) nanosphere delivery system decorated with cell penetrating peptides (CPPs) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Guler et al investigated multicomponent peptide amphiphile (PA)/oligonucleotide sytems for intracellular delivery of AONs. 622 PAs were designed that included N -terminal lauryl groups attached to a P 4 polyproline with C -terminal olignoculeotide-binding/cell penetrating motifs (Figure 49A). These self-assembling PAs were found to form spherical particles that bound AONs at the solvent exposed exterior face (Figure 49B).…”
Section: Peptide/biopolymer Hybridsmentioning
confidence: 99%
“…Guler et al investigated multicomponent peptide amphiphile (PA)/oligonucleotide sytems for intracellular delivery of AONs. 622 PAs were designed that included N -terminal lauryl groups attached to a P 4 polyproline with C -terminal olignoculeotide-binding/cell penetrating motifs (Figure 49A). These self-assembling PAs were found to form spherical particles that bound AONs at the solvent exposed exterior face (Figure 49B).…”
Section: Peptide/biopolymer Hybridsmentioning
confidence: 99%
“…3,52,53 For example, Moyer et al 11 have shown that the location and length of the alkyl tail can drastically alter the morphology of pH-responsive, self-assembled peptide amphiphile systems, and that cylindrical nanobers had around 7-fold higher encapsulation efficiency for camptothecin compared to spherical assemblies. In contrast, Mumcuoglu et al 54 demonstrated that cell-penetrating peptide nanospheres were uptaken by the cells more compared to nanobers because peptide nanobers bound strongly to the cellular membrane and were internalized to a lesser degree by the cells. In addition, two lysine-rich peptides were shown by Newcomb et al 55 to exhibit markedly different cytotoxic effects depending on their hydrogen bonding interactions, with the H-bond-rich b-sheet forming peptide showing minimal toxicity and the H-bond-poor sequence rapidly disrupting the integrity of both cell membranes and liposomes.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, integration of CPP to the vectors or peptide nucleic acid conjugates can be used for internaliza tion (Jung et al, 2011). Recently, CPP-decorated self-assembled peptide amphiphile (PA) nanospheres complexed with antisense oligonucleotides increased the internalization of the nanosized delivery system compared to nonbioactive PA nanostructures (Mumcuoglu et al, 2015).…”
Section: Cellular Internalization Strategiesmentioning
confidence: 99%